Enhancing Critical Thinking in Optics through Project-Based STEAM Learning with Visual Simulations - Al Anshori, Imam; Parno, Parno; Hidayat, Arif; Ali, Marlina (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
Optical material is widely applied in everyday technology but remains difficult for students to grasp due to its abstract nature. This challenge is linked to students’ low critical thinking skills—an essential 21st-century competence. This study aims to enhance students' critical thinking on optical topics through the integration of project-based learning with a STEAM approach and visual simulation media (PjBL-STEAM-MSV). A mixed-method design with an untreated control group and pretest-posttest was employed. The participants were 54 students from SMAN 1 Woha, NTB, Indonesia, divided into an experimental group (PjBL-STEAM-MSV) and a control group (conventional instruction). Data collection used a critical thinking essay test (5 items, reliability = 0.636) and interview guidelines. Quantitative data were analyzed using t-tests, N-gain, and effect size; qualitative data through reduction, coding, and interpretation. Results indicated that PjBL-STEAM-MSV significantly improved students’ critical thinking in optics (α = 0.01). The experimental group's N-gain score was 0.48 (moderate), higher than the control group’s 0.20 (low). The most notable improvements in the experimental group were in evaluation and explanation, while in the control group, gains were limited to analysis and explanation. Experimental group students struggled with explanation during presentations due to time constraints, whereas the control group showed difficulty across most indicators due to a focus on rote learning. Interviews revealed that experimental group students experienced more active, interactive, and structured learning. This aligns with the high effect size of 1.7. Further research should explore media development and sustained student mentoring to maximize outcomes.